An Analysis of Food Security Indicators and Stunting in Bengkulu Province, 2021–2023 - Rizky, Aulivia Ahma; Zulhadiman; Yanhari, Apriza Dqi; Tanziha, Ikeu (JAND: Journal of Applied Nutrition and Dietetic, 2025)
Stunting remains a significant public health concern in Bengkulu Province. According to the 2023 Indonesian Health Survey (IHS), the prevalence of stunting in Bengkulu reached 20.2%. This study analyzes the relationship between stunting and food security indicators using secondary data from the Bengkulu Central Statistics Agency and the National Food Agency from 2021 to 2023, comprising 30 samples. The analysis showed no statistically significant relationship between stunting and any of the independent variables at the 95% confidence level. The p-values for all variables—including the Food Security Index (FSI), Nutritional Consumption Pattern Ratio (NCPR), poverty rate, food and electricity expenditures, access to clean water, average years of schooling, health worker ratio, life expectancy (AHP), Desirable Dietary Pattern (DDP), Energy Adequacy Ratio (EAR), and Protein Adequacy Ratio (PAR)—were above 0.05. These findings suggest that none of the examined indicators had a significant effect on stunting in Bengkulu Province during the study period.